Dictogloss Approach to Dictation Writing Activities - Ghaltakhchyan, Siranoush (Armenian Folia Anglistika, 2016)
The present article is devoted to the study of modern approaches to dictation writing activities, namely to dictogloss approach, the purport of which is, first and foremost, to build a solid foundation of the English language proficiency and enhance integrated language skills in context. As different from traditional dictation writing activities, that aim at helping language learners become accustomed to processing and differentiating between different sounds of the target language, identifying words and phrases and recording them as accurately as possible, the dictogloss method of dictation writing tries to boost listening for detailed understanding, i.e. focusing on the grammatical constructions used in the texts, guessing the words and phrases suitable to the context, constructing meaning from the recorded texts and interpreting the gist of the dictated stories. Our study shows that the effectiveness of dictation writing activities in EFL classroom increases and the dictogloss procedure becomes more enjoyable and challenging in case of the intensive use of authentic materials, i.e. when the texts are not dictated directly by the teachers themselves, but are told by native speakers recorded on CDs.